Nowe technologie w systemie ochrony zdrowia na przykładzie Stanów Zjednoczonych i Polski - Cuda, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The main purpose of this paper is to present the level of new technologies implementation in the healthcare systems in US and Poland. New technologies play a crucial role in everyday life, including healthcare. Medical documentation and easy access to potentially life-changing or lifesaving information are extremely important for all the stakeholders in the healthcare system — its preparation, archiving and effective use in real time upon request may be supported by advanced systems. IT systems may improve security, medical services quality and efficiency of medical treatment, regardless of the type of healthcare system — private in the US and public in Poland. The results of surveys conducted by the American Society of Health-System Pharmacists and the Polish Centrum Systemów Informacyjnych Ochrony Zdrowia [Center of Healthcare Information Systems] have been used in this paper
Keywords: digitalizacja; transformacja cyfrowa; innowacje; system opieki zdrowotnej; usługi medyczne; ochrona zdrowia; elektroniczna karta pacjenta; pacjenci